Numerical Simulation of Thermal Field in Mass Concrete With Pipe Water Cooling - Zhu, Fuxian; Chen, Guorong; Zhang, Feng; Li, Qingwen (Frontiers in Physics, 2021)
Water pipe cooling is mainly used to control temperature during the construction of mass concrete structures. How to accurately simulate the temperature field of mass concrete under the action of water pipe cooling is very important. This paper presents a new method for simulating the temperature field of a mass concrete with the water pipe cooling. In this method, the contact surface of the water pipe and the concrete is used as the heat dissipation surface into the control equation, and the composite Multiquadrics radial basis function (MQ-RBF) and low-order linear polynomial combination are used to discrete the spatial domain. Because the heat dissipation surface of the water pipe is included in the boundary conditions, there is no need to build the refined water pipe modelling. This new method not only reduces the calculation cost, but also ensures the calculation accuracy. Through four calculation examples, they show that the algorithm has advantages in the numerical simulation of the concrete temperature field with water pipe cooling.